Letter to candidates for the State Assembly 36th District from Chuck Thomas - Chuck Thomas::::::
This letter from the Ventura County Star-Free Press is addressed to all candidates for the 36th District State Assembly race. The newspaper requests campaign materials in advance of the June 8 primary to provide equal-time coverage for voters. Candidates are asked to submit a recent passport-style photo, a biographical sketch, a 250-word statement similar to a ballot statement, and answers to an enclosed questionnaire on key Assembly issues. The paper assures candidates that editing will be minimal and limited mainly to spelling and punctuation to fairly represent their views. All materials are requested by April 19, and the letter is signed by Chuck Thomas, Executive Editor.